Writing (hi)story : Gascony in Jean Froissart’s chroniques - Souleau, P (2014)
Jean Froissart’s Chroniques, composed of four Books, relate the first stages of the Anglo-French conflict later known as the Hundred Years’ War (1337–1453). This thesis explores Froissart’s textual journey(s) to Gascon lands (south-west of modern-day France) and history/stories. Relying on Gérard Genette’s and Mikhail Bakhtin’s narrative theories, it uses literary and narratological tools to analyse three passages from Book I and III concerned with Gascony: the Earl of Derby’s Gascon campaigns (Chapter 1); the Black Prince’s Gascon campaigns and the principality of Aquitaine (Chapter 2); Froissart’s personal journey to and stay at the court of Gaston Fébus, count of Foix-Béarn (Chapter 3). One aim of the study is to investigate the representation of the region but it also argues that the Gascon passages have wider implications for the Chroniques, Froissart’s work as a whole, and the writing of history in the fourteenth century. At the turn of the twentieth century, Froissart’s ‘history’ was often disparagingly discussed by scholars due to factual inaccuracy and literary embellishments: such a ‘historical narrative’, it was felt, fell short of history and was nothing more than an entertaining story presenting outdated chivalric ideals. Although this approach has been partly revised, some critics still view the Chroniques’ earlier Books as being a narratively straightforward reflection of such a chivalric ideology, lacking critical hindsight on fourteenth-century events and society, and thus presenting paradoxical and irreconcilable tensions with later Books to the extent that they are occasionally deemed to be an entirely different kind of work than their later counterparts. The narrative thread of Froissart’s Gascon (hi)story explored here allows the revision of such views and shows that Froissart’s narrative is far from narratively and ideologically straightforward. This complexity is present as early as the first versions of the Book I, which should be envisaged in parallel, not in opposition, with the ‘later’ Chroniques. Similarly, the various tensions (e.g. fiction/history; ideal/real) underpinning the whole work, manifested in the portrayal of Gascony/the Gascons, are best approached in terms of co-existence, not antagonism. Such a multi-faceted work (a mirror and/or product of the fourteenth century?), à mi-chemin between history and fiction, between conflicting yet co-existing perspectives, is precisely what makes Froissart’s Chroniques valuable to literary critics, philologists, and historians alike.